2021
DOI: 10.1002/ppp3.10211
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying apple diversity: A phenomic characterization of Canada’s Apple Biodiversity Collection

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 62 publications
1
35
1
Order By: Relevance
“…Further, each variable in PCA should ideally capture an independent biological feature of apples. However, some phenotypes analysed here are correlated, such as harvest date and firmness [ 23 ], and their variation may be driven by the same biological feature [ 27 ]. Therefore, interpreting our PCA as a quantification of the degree of phenotypic differentiation between cultivated and wild apples should take these caveats into consideration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, each variable in PCA should ideally capture an independent biological feature of apples. However, some phenotypes analysed here are correlated, such as harvest date and firmness [ 23 ], and their variation may be driven by the same biological feature [ 27 ]. Therefore, interpreting our PCA as a quantification of the degree of phenotypic differentiation between cultivated and wild apples should take these caveats into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotype data analysed here were collected from Canada’s Apple Biodiversity Collection (ABC) and were part of previously published work [ 23 ]. Briefly, the ABC is an apple germplasm collection located at the Agriculture and Agri-Food Canada (AAFC) Kentville Research Station in Nova Scotia, Canada (45.071767, -64.480466).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On average, elite material is also harvested later than genetic resources, most probably because fruits with a later ripening are more firm (Migicovsky et al 2016) and can be stored longer (Nybom et al 2008). Modern varieties also have a lower phenolic content than genetic resources in general (Ceci et al 2021;Watts et al 2021). A recent pedigree reconstruction study showed that the two populations are separated by approximately 5-10 generations (Muranty et al 2020), which could result in the persistence of marker phase and effects across populations.…”
Section: Potential Of Combining Populationsmentioning
confidence: 99%